Review and Assessment of Programs Offered by State Universities and Colleges - Rosario G. Manasan (Philippine Institute for Development Studies (PIDS), 2013)
Given the importance of tertiary education in promoting human development and improving the economy's competitiveness, the state universities and colleges (SUCs) in the Philippines have always faced issues on the quality of education, management, and access. This study aims (i) to review and assess the programs being offered by SUCs vis-\~A -vis their mandates, the courses being offered by other SUCs in the region, and the quality of graduates produced; and (ii) given the findings, to recommend courses of action to improve the relevance and quality of course offerings of the SUCs.A review of the mandates of the various SUCs in the selected regions covered by this study (Regions IV-A, VII, XI, and VI, respectively) indicates that the mandates of a number of SUCs are fairly broad to start with. Also, many SUCs offer programs outside of their core mandates because the charters of most SUCs allow them to. Given these broad mandates, it is expected that there is substantial duplication in their program offerings relative to those of private higher education institutions (HEIs) and other SUCs in the same region. Moreover, high rates of program duplication appeared to be associated by an increase in the number of programs offered by SUCs. Program duplication may be considered a problem because of its tendency to increase per student cost of SUCs and the issue of SUCs crowding out private higher education institutions (PHEIs). Many PHEI officials also report that while the Commission on Higher Education (CHED) strictly enforces its Policies, Standards and Guidelines (PSGs) on PHEIs, the same rules are not applied as strictly on SUCs. Furthermore, the low quality of instruction is evident in the poor performance in the professional board examinations (PBEs). The median passing rate for 36 PBEs for 2005-2010 ranged from 40 percent to 45 percent during the period. Additionally, only 7 out of these 36 PBEs had average passing rates above 60 percent and only two have passing rates above 70 percent. There is also a preponderance of SUCs/PHEIs with zero passing rate in many PBEs and passing rates that are below the national average passing rate in 2005-2010.Given these findings, it is recommended that (i) the CHED enforces more vigorously its policy of closing existing programs of SUCs and PHEIs alike where these HEIs' performance is under par year after year; (ii) the CHED ensures that SUCs' program offerings comply with its PSGs; (iii) the CHED weighs the advantages/disadvantages of centralization over decentralization with respect to the monitoring of SUCs; (iv) the CHED regional director becomes a regular member of the SUC Board; (v) the normative funding formula is adjusted so that SUCs do not get an additional subsidy from the national government for the additional enrollment resulting from their offering popular programs (i.e., SUCs may be allowed to offer popular programs provided they meet CHED standards and shoulder the full cost of doing so); and (vi) in order to uplift the overall quality of instruction, the more effective measures, such as faculty development and facilities upgrading, be considered.
Keywords: 330; Philippines; state universities and colleges (SUCs); private higher education institutions (PHEIs); program offerings; mandates; duplication; board exam; passing rates; quality; budget